Laju Parasitasi Parasitoid Anagrus sp. dan Oligosita sp. terhadap Telur Wereng Coklat setelah Aplikasi Insektisida di Pertanaman Padi - MUNAWAR, DEDE; ISWANTO, EKO HARI; SUMARYONO, NONO; EFFENDI, BAEHAKI SUHERLAN (Agrotrop : Journal on Agriculture Science, 2015)
Parasitism rate of Anagrus sp. and Oligosita sp. parasitoids to brown planthopper eggs after insecticides application in the rice field. The research wascarried out in Subang District, West Java in the wet season of 2013. The experiment used arandomized block design with 7 insecticide treatments and four replications. The treatmentswere rynaxypyr, fipronil, imidakhloprid, dinotifuran, pimetrozin, and BPMC compared withcontrol. The objective of the research was measuring parasitism rate of parasitoids to brownplant hopper (BPH) eggs after insecticides application. The results showed that rynaxypyr,dinotefuran, and imidacloprid quickly reduced the BPH population only in one day afterapplication (DAA), while fipronil, pimetrozin, and BPMC were rather slow because the BPHdeclined in 10 DAA. All insecticides were give a negative effect to Anagrus sp. and Oligositasp parasitoids, but the performance of those parasitoids back to normal in 10 DAA forAnagrus sp. and in 21 DAA for Oligosita sp. The parasitism rate of all parasitoids were give anegative value in 1-10 DAA. In 21 DAA the parasitism rate of Anagrus sp. increased infipronil, BPMC and dinotefuran treatment, but the parasitism rate of Oligosita sp. were still innegative value under the control treatment.
Keywords: eggs parasitoid; parasitism rate; brown plant hopper